INVESTIGATION ON THE MECHANICS OF PRECAST SEGMENT TUNNEL LINING (Jurnal Teknologi (Sciences & Engineering), 2016)
Tunnel lining design is an interactive problem, which is not merely about the strength, but how much the lining could deform to accommodate the ground movement.Â  When tunnel interacts with soil, stress from the ground is distributed onto the structure. In precast segmental tunnel lining, it is critical to investigate the lining reaction when applied with load, as this affects the overall flexural behaviour of tunnel lining. The objective of this paper is to understand the basis of tunnel lining mechanical behaviour response. A series of conducted flexural bending laboratory testing and developed numerical models presented here in order to discuss on the mechanics of segmental tunnel lining. By having two different support mechanisms, variation trend in load-deflection and moment bending curve depicted.Â  Mirror trend of pin-pin support can easily be spotted in the results indicated segment lining affected by the load and support design.Â